ANALYSIS OF THE MOTHER’S ROLE IN THE SEXUAL DEVELOPMENT OF ADOLESCENT GIRL WITH INTELLECTUAL DISABILITIES AT UPT SLB-E NEGERI PEMBINA PROVINCIAL LEVEL OF NORTH SUMATRA IN 2025 - Syakila Khairunisa; Asfriyati Asfriyati; Maya Fitria; Fitri Khairani (Pusat Studi Gender dan Anak, 2025)
Background: Adolescents with intellectual disabilities face significant challenges in understanding sexual and reproductive health (SRH) due to cognitive limitations, stigma, and lack of appropriate education. Parents, particularly mothers, play a central role in supporting their daughters’ self-care and protection during puberty. Objective: This study aimed to explore the lived experiences of mothers in providing sexual and reproductive health education to adolescent girls with intellectual disabilities. Methods: A qualitative phenomenological approach was used, involving in-depth semi-structured interviews with five mothers selected through purposive sampling. Data were analyzed using Colaizzi’s method, followed by member checking, triangulation, and audit trails to ensure credibility. Ethical approval was obtained from the Health Research Ethics Committee of Universitas Sumatera Utara. Results: Five main themes emerged: (1) mothers’ emotional journey, (2) understanding of sexual and reproductive health, (3) communication and parenting strategies, (4) social and cultural barriers, and (5) support and coping mechanisms. Mothers experienced mixed emotions—fear, shame, love, and responsibility—while navigating social stigma and limited knowledge. Conclusion: Mothers’ experiences reflect the complexity of raising daughters with intellectual disabilities within cultural and religious contexts. The findings highlight the importance of inclusive, family-centered SRHR education and psychological support to empower parents in guiding and protecting their children.